Simply Chakras - Fenton, Sasha (New York Sterling/zambezi, 2009)
Contents:A brief history -- About chakras -- What use are chakras? -- The base chakra -- The sacral chakra -- The solar plexus chakra -- The heart chakra -- The throat chakra -- The brow chakra -- The crown chakra -- Physical chakra healing -- Emotional or mental chakra healing -- Further chakras -- Chakras and astrology -- Kundalini
index
Keywords: Chakras; Yoga